Penerapan Evidence Based Practice Terapi Pursed Lips Breathing Pada Anak Bronkopneumonia Dengan Masalah Bersihan Jalan Nafas Tidak Efektif - Mait, Hana Maria Ferlinda; Legi, Julita (JURNAL ILMIAH KESEHATAN MANADO, 2025)
Based on the health profile in 2019, approximately 52.9% of the total number of children suffer from bronchopneumonia. West Papua has 129.1% of children with bronchopneumonia cases, DKI Jakarta 104.5%, North Kalimantan 67.9% and Sulawesi reaching 86.2%. Breathing exercises in children using the pursed lips breathing method are used to remove secretions and free air trapped in the lungs. Knowing pursed lips breathing in pediatric patients with bronchopneumonia focuses on adjusting the respiratory system for ineffective airway clearance. This research method uses a case study method with a single case nursing care approach as the unit of analysis. The unit of analysis is a pediatric client with bronchopneumonia with an intervention of providing pursed lips breathing for 15 minutes in pediatric patients with bronchopneumonia. Based on the results of the existing assessment, the priority diagnosis was found to be Ineffective Airway Clearance (D.0001) associated with airway hypersecretion. The application of Pursed Lips Breathing that has been carried out on pediatric patients with Bronchopneumonia can be concluded that Pursed Lips Breathing can help slow breathing, increase respiratory efficiency and reduce shortness of breath.